Effects of the home-based educational intervention on health outcomes among primarily Hispanic children with asthma: a quasi-experimental study - Juha Baek; Ke Huang; Lucia Conner; Niko Tapangan; Xiaohui Xu; Genny Carrillo (BMC, 2019)
Abstract Background Childhood asthma is a significant health issue with 8.3% prevalence in the U.S. Its prevalence is particularly higher among low-income communities in the Texas-Mexico border region, as they often lack access to clinical care and health insurance. This study examines the impact of a home-based education led by Community Health Workers (CHWs) on health outcomes for asthmatic, predominantly Hispanic children in these communities. Methods The study was a quasi-experimental design to learn the effectiveness of the asthma home-based education by comparing changes of health outcomes between baseline and follow-up of intervention and control groups. This study enrolled 290 participants, consisting of 130 in the intervention group and 160 in the control group. The educational intervention led by the CHWs referenced the Asthma and Healthy Homes curriculum and contents of the Seven Principles of Healthy Homes. The multiple linear regression analysis was conducted to estimate the associations between the intervention and each health outcome. Results When comparing the intervention group with the control group, the intervention group showed a significantly greater decrease in asthma attacks than the control group (p = 0.049). Although all of the five Children's Health Survey for Asthma (CHSA) scores showed significant improvements between baseline and follow-up in both groups, we found that increases of CHSA scores in the intervention group were higher than the control group except for emotional health of children (EC) score. The multiple linear regression models demonstrated that the mean changes in asthma attacks (p = 0.036) and emotional health of families (EF) score (p = 0.038) were significantly better in the intervention group than the control group, adjusting for children's age of diagnosis, household income, use of steroids, family history of allergy, and type of insurance. Conclusions This study concluded that the home-based education by CHWs effectively improve health outcomes among children in communities lacking access to medical resources. The findings suggest the importance of the home-based education program in promoting emotional and medical care for children and their families in low-income communities like those in the Texas-Mexico border region.